Peran Media Sosial dalam Meningkatkan Ekonomi Masyarakat (Pada Warga Pulai Payung Kelurahan Surabaya Kecamatan Sungai Serut Kota Bengkulu) - Ida Anggriani; Ermy Wijaya; Suwarni Suwarni; Ahmad Soleh; Nurzam Nurzam (Jurnal Dehasen Untuk Negeri, 2022)
Currently, social media is a good medium for economic actors in doing marketing, this is due to easy internet access and is supported by the large number of internet media users in Indonesia. Currently, online business is a strength in developing its business, especially during this covid-19 pandemic where people must obey the rules implemented by the government such as social distancing, implementing community activity restrictions (PPKM). Social media is currently contributing to people who want to do business activities by utilizing social media, this is evidenced by the existence of platforms provided by several social media to carry out business promotion activities, for example the existence of WhatsApp with business accounts, Instagram business accounts, Facebook business pages. , and there are also promotional features provided on each of these social media at a very low cost when compared to using television and print media such as newspapers to carry out promotional activities. The community service program carried out by the team is an activity carried out to provide training to the residents of Pulai Payung Rt 12 Rw 04, Surabaya Village, Sungai Serut District, Bengkulu, so that they can take full advantage of social media, especially in improving the community's economy, where social media can basically be utilized. as a business account to carry out promotional activities or media to be more easily connected to a wider network when compared to conventional businesses that do not use social media at all.